EXPERIENCE OF THE ADALIMUMAB APPLICATION FOR THE PATIENT WITH EARLY DEBUT OF JUVENILE IDIOPATHIC ARTHRITIS AND UVEITIS - K. B. Isaeva; E. I. Alexeeva; R. V. Denisova; T. V. Sleptsova; Т. М. Bzarova; S. I. Valieva; E. V. Mitenko; E. G. Chistyakova; А. М. Chomakhidze (Вопросы современной педиатрии)
The case of early debut and heavy course of juvenile idiopathic arthritis in the patient at the age of 1 year and 8 months, associated with uveitis refractory to the therapy by methotrexate and nonsteroid antiinflammatory preparations is presented. The given clinical example shows high therapeutic efficiency of the adalimumab. To the 8th week of treatment inflammatory changes in conjunctiva were stopped, to the 12th week the stage of inactive illness was registered, i.e. the patient had no inflammatory changes in joints, uveitis activity signs, increase of laboratory indicators of illness activity. Duration of remission of articulate syndrome and uveitis made 9 months.